Phosphorylation induces a decrease in the biological activity of the protein inhibitor (GABA-modulin) of gamma-aminobutyric acid binding sites. - Wise, B C (1983)
gamma-Aminobutyric acid (GABA)-modulin is a brain protein of Mr 16,500 that down-regulates the high-affinity binding site for GABA which is located in crude synaptic membranes. This protein can be phosphorylated in vitro by the catalytic subunit of cAMP-dependent protein kinase and by a partially purified preparation of calmodulin-sensitive Ca2+-dependent protein kinase. The GABA-modulin sites that are phosphorylated by the two enzymes are different, as revealed by HPLC analysis of tryptic digests. The capacity of GABA-modulin to decrease the number of sites that bind [3H]muscimol was completely abolished by phosphorylation of this protein with the cAMP-dependent protein kinase but not with the Ca2+-dependent enzyme. GABA-modulin present in crude synaptic membranes prepared from rat cortex also was shown to be phosphorylated by endogenous protein kinases activated by cAMP, Ca2+ and calmodulin, and Ca2+ and phosphatidylserine. These results suggest a potentially important role for protein kinase and GABA-modulin in the regulation of the number of GABA recognition sites.